Controlled‐Release Nitrogen Fertilizer Improved Lodging Resistance and Potassium and Silicon Uptake of Direct‐Seeded Rice. Issue 6 (1st November 2019) - Zhang, Shugang; Yang, Yuechao; Zhai, Weiwei; Tong, Zhaohui; Shen, Tianlin; Li, Yuncong C.; Zhang, Min; Sigua, Gilbert C.; Chen, Jianqiu; Ding, Fangjun
ABSTRACT: Lodging is a severe problem for rice ( Oryza sativa L.) because it interferes with mechanical harvesting, and potentially results total crop loss. This study investigated whether a controlled‐release urea (CRU) could reduce lodging, improve the uptake of K and Si, and yields of direct‐seeded rice. The 2‐yr field experiment included four rates of CRU (120, 180, 240, and 360 kg N ha −1 ), each provided in one application; a conventional urea fertilizer provided in four applications (360 kg N ha −1 total); and a control with no N fertilizer. Results indicated that the N release rates from the CRUs were matched well to N uptakes by rice plants; hence, N use efficiencies were improved. Concentrations of K and Si in rice tissues were much higher for treatments with the full and reduced rates of CRU than for the full rate urea treatment. Lodging of rice only appeared to occur in the urea treatment. Microscopic examination revealed that cells of rice stems provided with CRU treatments were more resistant to lodging than stem cells from plants in the urea treatment.